Hormonal and reproductive factors and reduction in the risk of colorectal cancer. Issue 3 (May 2020) - Rennert, Gad; Rennert, Hedy S.; Pinchev, Mila; Gruber, Stephen B.; Lavie, Ofer
Abstract : Females differ from males in incidence and clinical characteristics of colorectal cancer. Understanding the differences can lead to development of preventive approaches. To identify reproductive factors currently associated with the risk of colorectal cancer. Consecutively diagnosed female colorectal cancer cases and randomly chosen colorectal cancer-free controls matched on age/ethnicity/primary care clinic within the molecular epidemiology of colorectal cancer study, a population-based case-control study in Northern Israel, were included. A total of 2867 female cases and 2333 controls participated in this analysis. Participants were interviewed on reproductive history: ages at menarche, menopause, first birth, terminations of pregnancies, miscarriages, births, use of oral contraceptives. Among 5200 women, spontaneous miscarriages (odds ratio = 0.71, 0.61–0.83 for ever/never in Jews; odds ratio = 0.76, 0.53–1.08 in Arabs) and number of miscarriages, but not termination of pregnancies, as well as use, and duration of use, of oral contraceptives (Jews: odds ratio = 0.49, 0.39–0.62 for ever/never; Arabs: odds ratio = 0.14, 0.04–0.47) were strongly inversely associated with colorectal cancer risk. Up to 5 pregnancies were associated with increased risk while ages at menarche, at menopause and at first birth were not associated with colorectal cancer risk. Miscarriages but not terminations of pregnancy or full-term pregnancies, and use of oral contraceptives, were strongly associated with reduced odds of developing colorectal cancer suggesting unique hormonal influences on colorectal cancer.